MENINGKATKAN HASIL BELAJAR BOLA VOLI MINI MELALUI TUTOR SEBAYA SISWA SEKOLAH DASAR (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of the study to determine the learning outcome volleyball mini through peer tutoring approach for fourth grade students Sabarwangi District Subdistrict Kajen Pekalongan.Reseach using action research. The subjects used were fourth grade students of SD Negeri 23 Sabarwangi the number of students consisting of 14 boys and 9 student daughter .Tecnic with observations and data collection dokumentasi.Instrumen used in the data collection was obtained from the test results that show student performance when implementation. Based on the above results, it can be concluded that the application of mini volleyball lessons through peer tutoring approach has a positive effect, which can increase the yield student learning that can facilitate students to understand and perform the movement correctly. Suggestion of this study can be used as an alternative learning materials if there were teachers who experience the same learning problems.